LEGAL CONSEQUENCES OF NON-ANTHROPOGENIC IMPACT ON THE ENVIRONMENT - T. B. Nevzorov (Вестник Кемеровского государственного университета, 2014)
The paper aims at primarily defining thelegal boundaries of this problem. The authorproposes to recognite the introduction  of  emergency  situation  and  state  of  emergency  as  the  main  legal  consequences  of  negative  nonanthropogenic impact on the environment.